2006ネン ナンキョク イガク イリョウ ケンキュウ シュウカイ ホウコク - 大野, 義一朗; オオノ, ギイチロウ; 大日方, 一夫; オビナタ, イチオ; 下枝, 宣史; シモエダ, ノブヒト; 大谷, 眞二; オオタニ, シンジ; 宮田, 敬博; ミヤタ, タカヒロ; 藤原, 久子; フジワラ, ヒサコ; et al. (2007)
P(論文) 南極医学医療研究集会は,わが国の南極医学研究と医療問題についての研究成果を報告・討論し,次期の観測隊における医学研究に寄与することを目的として毎年行われている.2006年の本研究集会は8月26日,国立極地研究所講堂で行われた.27施設から42名が参加し18の演題報告がなされ,近年では最大規模の研究集会となった. 参加者は越冬経験医師をはじめ,共同研究を行っている大学や研究機関の研究者,関連領域の研究を行っている宇宙開発機構やスポーツ科学研究所などの研究者,南極に興味のある一般病院の臨床医など多彩であった. 2004年より昭和基地に導入されたテレビ会議システムを活用して,昭和基地の医師もリアルタイム映像で討論に参加した.また韓国,中国の越冬医師が初めて参加した.これは3カ国の極地研究所による事前の準備と連携により実現した.集会では各国の南極基地の医療状況や医学研究活動が報告され,活発な意見交換がなされた.南極医学医療研究分野におけるアジア連携の端緒となることが期待される. A workshop on Antarctic Medical Research and Medicine 2006 was held at the National Institute of Polar Research (NIPR) on 26 August, 2006. Forty two participants from 27 institutes attended. The members consist of medical doctors with Antarctic experience, human biologists, research scientists in other fields, logistic staff members of the expedition and also medical doctors interested in Antarctica. The current resident doctor at Syowa Station joined the discussion through a telecommunication system. Doctors with Antarctic experience from China and Korea also participated in the workshop. They gave presentations on their Antarctic activities, followed by an active discussion session. Eighteen presentations were given on various topics, including the International Polar Year (IPY) 2007-2008 in medical research, space medicine, telemedicine, an international comparative study of medical operations, psychological surveys, Antarctic high-altitude medicine, Legionella surveillance and nutritional studies. departmental bulletin paper